En torno al género literario de la confesión - Wachowska, Judyta (Studia Romanica Posnaniensia, 2001)
The present article tries to explain some points of the generic definition of confession, showing that there are some determinant factors that allow to distinguish it from the autobiography such as: thematic space, reason and/or narralaire and treatment of time and memory.